Synthesis, Characterization and Antimicrobial Activity of Some New Thiazines - Srinivasa Murthy, M.; Mohan, S. (Asian Journal of Chemistry, 2010)
Cyclohexanone on Claisen-Schmidt condensation with various aromatic aldehydes in presence of dilute sodium hydroxide affords the corresponding 2,6-diarylidene cyclohexanones (1). Further, these compounds (1) were subjected to cyclocondensation with thiourea, catalyzed by aqueous potassium hydroxide to form 4-aryl-8-arylidene-2-imino-5,6- dihydro-4H,7H-(3,1)benzothiazines (2). The structures of synthesized compounds were characterized by their spectral studies and the antimicrobial activity of 2 was also evaluated.